CRIME MODE OF FRAUD TRANSFER OF FUNDS USING ANOTHER PERSON’S IDENTITY - Abimanyu Pratama; Neri Widya Ramailis (Sisi Lain Realita, 2024)
This research aims to find out the role of victims in the occurrence of funds transfer fraud crimes and to find out efforts to overcome the occurrence of victims of funds transfer fraud crimes. The research was carried out in Pekanbaru City, on several victims and Riau Police investigators using the research method of conducting interviews with the parties involved. competent with the object of research, as well as requesting data from parties related to this research, the police and victims of fraud crimes. The results of this research show that the role of victims in fraud crimes has a fairly large role, because they give too much trust to the perpetrator and the lack of caution which results in the victim being easily victimized by the perpetrator of Fund Transfer fraud. Preventive efforts are efforts carried out before a criminal act occurs, or more precisely as an effort to prevent a criminal act. Efforts are made to prevent the occurrence of criminal acts of Fund Transfer fraud through socialization or reporting through the media and also through coordination with government and non-government institutions and other parties in the context of enforcing the law, as a forum for the public to know, so that if one person is deceived, another won't be fooled either. Other efforts are repressive efforts. Repressive efforts are actions taken by the police after the crime has occurred. Repressive efforts are carried out by following up on every report of a criminal act, including the crime of Fund Transfer fraud. Then provide strict legal sanctions against perpetrators of criminal acts, in order to provide a deterrent effect, in accordance with the sense of justice in society and legal certainty